The possibilities of using regional rail for intra-urban commuting in post-socialist cities in Central and Eastern Europe - Jurkowski, Wojciech; Kruszyna, Maciej (Bulletin of Geography. Socio-economic Series, 2025)
The main objective of this study is to explore the potential of using regional rail for intra-urban commuting in post-socialist cities of Central and Eastern Europe. The purpose of this study can be approached from cognitive and methodological perspectives. The cognitive objective is focused on the role of geographical and political conditions, while the methodological objective aims to propose and test a research procedure to assess to what extent existing regional train services can support urban rail transit. The study was conducted using examples from four cities in Central and Eastern Europe: Lviv, Riga, Wrocław, and Zagreb, as well as one from Western Europe (Leipzig), serving as a reference point for the analysis of research results. The main empirical part was conducted using nine indicators categorized into three groups: infrastructural, organizational, and developmental.